MODELLING REVERSIBLE INHIBITION OF IRREVERSIBLE ELECTRO-OXIDATION - lovric, Milivoj; Komorsky-Lovrić, Šebojka (Journal of the Chilean Chemical Society, 2020)
Totally irreversible electro-oxidation of dissolved reactant that is inhibited by the formation of oxide on the electrode surface is analysed theoretically. In the reverse, cathodic branch of staircase cyclic voltammogram these two parallel reactions exhibit both cathodic minimum and anodic maximum. The potentials of these extremes depend on the kinetics of oxide formation.